Proceedings of the 9th Annual Conference on Genetic and Evolutionary Computation 2007
DOI: 10.1145/1276958.1277013
|View full text |Cite
|
Sign up to set email alerts
|

Coevolution of intelligent agents using cartesian genetic programming

Abstract: A coevolutionary competitive learning environment for two antagonistic agents is presented. The agents are controlled by a new kind of computational network based on a compartmentalised model of neurons. The genetic basis of neurons is an important [27] and neglected aspect of previous approaches. Accordingly, we have defined a collection of chromosomes representing various aspects of the neuron: soma, dendrites and axon branches, and synaptic connections. Chromosomes are represented and evolved using a form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Although CGP has been used in various ways in developmental systems Miller and Thomson, 2003;Khan et al, 2007), the programs that it produces are not themselves developmental. Instead, these approaches used a fixed length genotype to represent the programs defining the behaviour of cells.…”
Section: Self Modifying Cartesian Genetic Programmingmentioning
confidence: 99%
“…Although CGP has been used in various ways in developmental systems Miller and Thomson, 2003;Khan et al, 2007), the programs that it produces are not themselves developmental. Instead, these approaches used a fixed length genotype to represent the programs defining the behaviour of cells.…”
Section: Self Modifying Cartesian Genetic Programmingmentioning
confidence: 99%
“…However, natural evolution does not work in this way, instead evolution operates at the very much lower level of genetic code and learning in organisms is an emergent consequence of many underlying processes and interactions with an external environment. The essential point here is that all learning occurs in the lifetime of the organism, a fact recently emphasized in [4,5]. From the point of view of this paper, the key point is that evolution has invented learning algorithms (inasmuch as physical learning processes can be simulated by algorithms).…”
Section: Introductionmentioning
confidence: 96%
“…In order to evaluate the eectiveness of this approach we have previously applied it to a classic AI problem called wumpus world [5]. We found that the agents improved with experience and exhibited a range of intelligent behaviours.…”
Section: Introductionmentioning
confidence: 99%